Self-harm in the two years of greatest restrictions during the covid-19 pandemic: a cross-sectional study - Odilon Vieira Santos; Letícia Aparecida Machado Lisboa da Silva; Meiry Fernanda Pinto Okuno; Paula Hino; José Ramón Martínez-Riera; Hugo Fernandes (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to analyze occurrence of self-harm, sociodemographic profile of victims and referrals in the first 24 months of the COVID-19 pandemic in São Paulo. Method: cross-sectional study carried out by the Notifiable Diseases Information System with data on self-harm in São Paulo. The period outlined was March 2020 to February 2022. R (4.0.2) software and chi-square test were used. Results: there were 15,946 incidents. Victims were young, white, single, heterosexual women. There was high incidence of people with previous mental disorders more than once and without clear motivation. The method used was poisoning/intoxication. There was a considerable number of referrals to the health network, although not totalitarian. Conclusion: the years of greater insecurity in relation to the pandemic have given rise to self-harm cases with peculiar characteristics. Agile health policies must be applied in atypical conditions, such as pandemics, especially for adolescents/young people with previous mental disorders.